(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Ad hoc networks are defined by a poor infrastructure as well as a spontaneous and quicklyshifting network topology, necessitating the use of a sturdy dynamic routing protocol that can cope withsuch conditions.The goal of this research is to evaluate the results of a few routing protocols for MobileAd-Hoc networks (MANETs). It is a group of wireless mobile nodes that establish a dynamic topologywithout the use of a logically centralized point, infrastructures, or management. Because the transmissionrange of nodes in MANETs is restricted, transmission of data across 2 nodes needs numerous hops.The scenario is made considerably more difficult by the mobility of the various nodes. Several protocolshave been proposed have been created specifically for these conditions in recent years to discover themost efficient routes from a sender to the receiver.This study compares and contrasts the performanceof 2 routing protocols (AODV DSDV). The simulations were run using Network Simulator II. The meanend-to-end delay is used to assess the performance of AODV DSDV.